Expression of Sport Experiences between Cadet and Junior Basketball Players (Baltic Journal of Sport and Health Sciences, 2021)
Background. The hypothesis of this study is formulated as follows: the experience of junior basketball players in competitions will be more valuable than that of cadet basketball players. The aim of our study was to examine the peculiarities of youth and basketball players’ sport experiences.Methods. A total of 104 basketball players, 47 cadets and 57 juniors participated in the study. Survey questionnaire is used for the study. The following methodologies were used: Athlete’s Personal Experience Survey (Athletic Coping Skills Inventory, ACSI-28) and the Sport Experiences Questionnaire (SEQ).Results. The results of the study revealed statistically significant differences (p